Improvement of performance and reduction of fatigue with low-level laser therapy in competitive cyclists - Lanferdini, F. J.; Bini, R. R.; Baroni, B. M.; Klein, K. D.; Carpes, F. P.; Vaz, M. A. (International Journal of Sports Physiology and Performance, 2018)
Evidence indicates that low-level laser therapy (LLLT) minimizes fatigue effects on muscle performance. However, the ideal LLLT dosage to improve athletes`performance during sports activities such as cycling is still unclear. Therefore, the goal of this study was to investigate the effects of different LLLT dosages on cyclists`performance in time-to-exhaustion tests. In addition, the effects of LLLT on the frequency content of the EMG signals to assess fatigue mechanisms were examined. Twenty male competitive cyclists participated in a crossover, randomized, double-blind, placebo-controlled trial. They performed an incremental cycling test to exhaustion (on day 1) followed by 4 time-to-exhaustion tests (on days 2-5) at their individual maximal power output. Before each time-to-exhaustion test, different dosages of LLLT (135, 270, and 405?J/thigh, respectively) or placebo were applied at the quadriceps muscle bilaterally. Power output and muscle activation from both lower limbs were recorded throughout the tests. Increased performance in time-to-exhaustion tests was observed with the LLLT-135 J (~22 s; P<.01), LLLT-270 J (~13 s; P=.03), and LLLT-405 J (~13 s; P=.02) compared to placebo (149±?23 s). Although LLLT-270 J and LLLT-405 J did not show significant differences in muscle activation compared with placebo, LLLT-135 J led to an increased high-frequency content compared with placebo in both limbs at the end of the exhaustion test (P=.03). In conclusion, LLLT increased time to exhaustion in competitive cyclists, suggesting this intervention as a possible nonpharmacological ergogenic agent in cycling. Among the different dosages, LLLT-135 J seems to promote the best effects.